Growth dynamics of transversal body dimensions and proportions, with related clinical determinants in children with X-linked hypophosphatemia treated with phosphate supplements and active vitamin D - Brieger, Laura Celine; Przygodda, Stephan; Bohlen, Alina Verena; Rehberg, Mirko; Konrad, Martin; Schlingmann, Karl Peter; Hiort, Olaf; Schmidt, Dorothee; John-Kroegel, Ulrike; Wühl, Elke; Kemper, Markus J.; Derichs, Ute; et al. (Pediatric nephrology, 2025)
Children with X-linked hypophosphatemia (XLH) present with rickets, leg deformities, and growth failure. Bone stability depends on balanced bone growth in both length and width. Data on body proportions, including transverse body dimensions, in children with XLH treated with phosphate supplements and active vitamin D are lacking.
Gesehen am 05.11.2025